Інноваційні технології формування професійного мислення інженера-механіка як засіб розвитку цілісної творчої особистості майбутнього фахівця - Панченко, О. І. (НТУ "ХПІ", 2015)
Статтю присвячено професійному розвитку особистості. Виявлено особливості професійної діяльності інженера в умовах сучасних новацій. Акцентовано увагу на необхідності змін в освітніх технологіях. Виокремлено основні інноваційні технології розвитку професійного мислення як засобу розвитку цілісної творчої особистості. Наголошено на необхідності застосування засобів інформаційної освіти.

The article deals with the problems of the professional development of a person. The features of the professional activity of engineer in a modern innovation were determined. We emphasize that the changes in educational technology is needed. The basic innovative technologies of the professional thinking development were determined as a means of developing an integrated creative personality. We outlined the necessity to use of means information education.
Innovative technologies of forming the future mechanical engineers professional thiking as a way to develop an integrated creative personality of the future specialist
Keywords: професійна підготовка; інноваційні освітні технології; професійна діяльність; вища школа; training